Enzymatic removal of N‐glycans by PNGase F coated magnetic microparticles. Issue 10 (15th March 2016) - Bodnar, Judit; Szekrenyes, Akos; Szigeti, Marton; Jarvas, Gabor; Krenkova, Jana; Foret, Frantisek; Guttman, Andras
Abstract : Investigation of protein glycosylation is an important area in biomarker discovery and biopharmaceutical research. Alterations in protein N‐glycosylation can be an indication of changes in pathological conditions in the medical field or production parameters of biotherapeutics. Rapid development of these disciplines calls for fast, high‐throughput, and reproducible methods to analyze protein N‐glycosylation. Currently used methods require either long deglycosylation times or large excess of enzymes. In this paper, we report on the use of PNGase F immobilization onto the surface of magnetic microparticles and their use in rapid and efficient removal of N‐glycans from glycoproteins. The use of immobilized PNGase F also allowed reusability of the enzyme‐coated beads as the magnetic microparticles can be readily partitioned from the sample by a magnet after each deglycosylation reaction. The efficiency and activity of the PNGase F coated magnetic beads was compared with in‐solution enzyme reactions using standard glycoproteins possessing the major N‐glycan types of neutral, high mannose, and highly sialylated carbohydrates. The PNGase F coated magnetic beads offered comparable deglycosylation level to the conventional in‐solution based method in 10‐min reaction times for the model glycoproteins of immunoglobulin G (mostly neutral carbohydrates), ribonuclease B (high mannose type sugars), and fetuin (highly sialylated oligosaccharides) with the special features of easy removal of the enzyme from the reaction mixture and reusability.